2024
DOI: 10.1001/jama.2024.2933
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Treatment Effects of Oxygen Targets in Mechanically Ventilated Critically Ill Adults

Kevin G. Buell,
Alexandra B. Spicer,
Jonathan D. Casey
et al.

Abstract: ImportanceAmong critically ill adults, randomized trials have not found oxygenation targets to affect outcomes overall. Whether the effects of oxygenation targets differ based on an individual’s characteristics is unknown.ObjectiveTo determine whether an individual’s characteristics modify the effect of lower vs higher peripheral oxygenation-saturation (Spo2) targets on mortality.Design, Setting, and ParticipantsA machine learning model to predict the effect of treatment with a lower vs higher Spo2 target on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Prior studies have shown that risk-based models can effectively measure variation in treatment effect. 38,39 This study suggests that, when possible, both risk-based and effect-based approaches should be tested when determining if an intervention should be targeted to a subset of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that risk-based models can effectively measure variation in treatment effect. 38,39 This study suggests that, when possible, both risk-based and effect-based approaches should be tested when determining if an intervention should be targeted to a subset of individuals.…”
Section: Discussionmentioning
confidence: 99%